Ocular surface cytokine profile in chronic Stevens-Johnson syndrome and its response to mucous membrane grafting for lid margin keratinisation. Issue 2 (8th July 2017) - Gurumurthy, Srividya; Iyer, Geetha; Srinivasan, Bhaskar; Agarwal, Shweta; Angayarkanni, Narayanasamy
Abstract : Background: To study the tear cytokine and the conjunctival and oral mucosal marker profile in chronic ocular Stevens-Johnson syndrome (SJS) and their alteration following mucous membrane grafting (MMG) for lid margin keratinisation (LMK). Methods: In a 1-year prospective study, SJS cases (n=25) and age-matched/sex-matched healthy controls (n=25) were recruited. Tear specimen (Schirmer's strip), conjunctival and oral mucosal imprints were collected from controls and SJS cases pre-MMG and post-MMG (at first follow-up, n=17). Tear cytokines were profiled using 27-bioplex array. Transforming growth factor-beta (TGF-β)-mediated extracellular matrix changes in conjunctival and oral mucosal cells were analysed by gene expression studies. 30 Results: Tear cytokine profiling of chronic SJS cases at pre-MMG stage revealed significant upregulation of cytokines granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin (IL)-8, IL-1β, monocyte chemoattractant protein-1, IL-15, IL-2, IL-17A and basic fibroblast growth factor (bFGF) with downregulation of IP-10 (interferon gamma-induced protein 10), tumour necrosis factor-α, interferon-γ, IL-10, vascular endothelial growth factor, regulated upon activation normal T-cell expressed and secreted (RANTES), IL-7, IL-12p70 and IL-13, with maximal increase in GM-CSF and maximal downregulation of IP-10, respectively. Of these, IL-2, IL-15, bFGF and IL-17A showed significant correlation with disease severity, pre-MMG. Conjunctival cells pre-MMG showed increase in TGF-β1, TGF-βRII, connective tissue growth factor and collagen-III gene expression by 10, 67, 173 and 184 folds, respectively, which dropped to 1.3, 11, 13.5 and 19 folds correspondingly, post-MMG. However, their expressions in oral mucosa were negligible. Conclusion: A proinflammatory, profibrotic, antiapoptotic ocular surface milieu characterises chronic ocular SJS. IP-10, an antifibrotic cytokine was noted to be maximally downregulated, unlike in other forms of chronic dry eye disease. The alterations in the ocular surface are seen to reverse largely with MMG for LMK.